2014
DOI: 10.1007/s11010-014-2120-5
|View full text |Cite
|
Sign up to set email alerts
|

The PPARβ/δ agonist GW0742 modulates signaling pathways associated with cardiac myocyte growth via a non-genomic redox mechanism

Abstract: Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that belong to the nuclear hormone receptor superfamily and appear to have beneficial effects in the cardiovascular system. PPARβ/δ has been shown previously to exert an inhibitory effect on cardiac myocyte hypertrophy in vivo and in vitro although the exact mechanism is not fully clear yet. The principal signaling pathways that have been involved in triggering cardiac hypertrophic response are mitogen-activated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Moreover, bioinformatic analyses of microarray and chromatin immunoprecipitation sequencing (ChIP‐seq) data revealed that ligand activation of PPARβ/δ with GW0742 did not cause changes in PTEN/ILK1/PDPK1 expression or promoter occupancy of PPARβ/δ on any of these genes in primary keratinocytes after ligand activation of PPARβ/δ as suggested by a previous study . These studies are also consistent with other experiments showing that ligand activation of PPARβ/δ with GW0742 or GW501516 in other cell types may actually increase PTEN expression and inhibit phosphorylation of AKT1 . Combined, the evidence that ligand activation of PPARβ/δ inhibits apoptosis in keratinocytes via modulation of PTEN/ILK1/PDPK1/AKT1 is inconsistent with many other studies, including those that have shown there is a unique form of programmed cell death associated with keratinocyte differentiation that differs substantially from apoptosis …”
Section: Pparβ/δ and Keratinocyte Programmed Cell Deathsupporting
confidence: 70%
“…Moreover, bioinformatic analyses of microarray and chromatin immunoprecipitation sequencing (ChIP‐seq) data revealed that ligand activation of PPARβ/δ with GW0742 did not cause changes in PTEN/ILK1/PDPK1 expression or promoter occupancy of PPARβ/δ on any of these genes in primary keratinocytes after ligand activation of PPARβ/δ as suggested by a previous study . These studies are also consistent with other experiments showing that ligand activation of PPARβ/δ with GW0742 or GW501516 in other cell types may actually increase PTEN expression and inhibit phosphorylation of AKT1 . Combined, the evidence that ligand activation of PPARβ/δ inhibits apoptosis in keratinocytes via modulation of PTEN/ILK1/PDPK1/AKT1 is inconsistent with many other studies, including those that have shown there is a unique form of programmed cell death associated with keratinocyte differentiation that differs substantially from apoptosis …”
Section: Pparβ/δ and Keratinocyte Programmed Cell Deathsupporting
confidence: 70%
“…They dimerize with retinoid X receptor (RXR) and bind to PPAR-responsive DNA regulatory elements controlling the expression of genes involved in adipogenesis, glucose, lipid, and cholesterol metabolism ( 9 , 10 ). Similarly to the membrane Estrogen receptorα (ERα), recently it has been demonstrated that PPARs can activate a non-genomic, rapid signaling pathway ( 11 , 12 ), but while several studies so far described the activation of the ER non-genomic, rapid pathway in response to potential EDCs ( 13 16 ), information regarding ability of pollutants to activate the PPAR-non genomic signaling is still lacking.…”
Section: Potential Mechanisms By Which Edcs Exert Their Effectsmentioning
confidence: 99%
“…PPARb/d agonists have been shown to hold therapeutic vasculogenic potential for the treatment of ischemic cardiovascular diseases through activation of PI3K/Akt pathway [146], whereas they also inhibit platelet aggregation and activation [147] via unidentified nongenomic mechanisms. A recent study provided the first evidence that the PPARb/d agonist GW0742 inhibits the phosphorylation of growth-related protein kinases in cardiac myocytes by modulating the activity of phosphatases through a nongenomic, PPARb/d-independent, redox mechanism [148].…”
Section: Nongenomic Effects Of Ppar Agonists In the Heartmentioning
confidence: 99%